Potential Utilization Analysis of River Waste in Jakarta, Indonesia - Rahajeng Hasna Safira; Mega Mutiara Sari; Suprihanto Notodarmojo; Takanobu Inoue; Regil Kentaurus Harryes (Department of Geography Education, University of Jember, 2021)
There are still many people in Jakarta who throw their garbage into the river, resulting Jakarta city never being absent from the problems of river water pollution and flooding. Pesanggrahan River and Grogol River are some of the big river surrounded by high popullation area. All waste originating from the Pesanggrahan River and the Grogol River is dumped into the Bantar Gebang Landfill. This study aimed to reduce waste entering landfills are by making use of waste that still has economic value.The method used in decision making from various alternatives of the river waste utilization are utility theory and compromise programming. It takes planning to find out the composition and generation of solid waste from those rivers and to determine the potential use of river waste and the action to minimize and handle the river waste. Utilization of river waste that can be applied based on the composition of most waste is open windrow composting and plastic shredding. It is important to concern about river waste since Indonesia has various polluted river, especially by solid waste. By implementing a good river waste utilization, the waste that enters the landfill will be reduced and in line with reduced pollution to the aquatic environment. Keywords: Solid waste; Water; Generation; Composition; Utilization Copyright (c) 2021 Geosfera Indonesia and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License